Gus Bahauddin Nursalim’s Speech and Language Politeness Strategy on YouTube - Zuhriyah, Siti Aminataz; Miftahulkhairah Anwar; Reni Nur Eriyani (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study aims to describe the form of language politeness strategies in Gus Bahauddin Nursalim's video lectures on Youtube. This research focuses on Gus Bahauddin Nursalim's lectures on Youtube, Santri Gayeng, with the most views in the last six months. This research uses a descriptive-qualitative approach that seeks to collect descriptive information and present it in text about the subject under study. The collected data is then analysed with Brown and Levinson's theory of language politeness. The results of this study show that there are 23 videos that fall into the category of language politeness strategies. The data shows a variety of positive politeness strategies, indirect strategies or vague speech, and straightforward strategies without preamble. The form of language politeness strategy is inseparable from Gus Baha's social influence in the community. He is known to have the characteristic of giving lectures with a speech that can have an influence on his listeners. Through the study of the language politeness of a preacher, this article contributes to the discussion of language studies and preacing activities in Indonesia.